0865 Dyadic Effects of Daily Stress and Satisfaction on Sleep Efficiency: A Preliminary Report among Colorectal Cancer Survivors and Their Spouses. (27th April 2018) - Ting, A; May, M; Mitchell, H; Carver, C; Kim, Y
Abstract: Introduction: Both cancer survivors and their spousal caregivers report substantially poor sleep quality. Studies have examined the effects of daytime stress and satisfaction in life on sleep quality, but these have been limited to the individual level and non-cancer populations. This study aimed to explore the degree to which daily stress and life satisfaction associated with sleep efficiency among colorectal cancer survivors and their spouses at the individual and dyadic levels across 14 days. Methods: Colorectal cancer survivors and their spouses ( n =20, 59 years old, 50% female) completed daily stress, life satisfaction, and sleep logs individually across 14 consecutive days. Perceived stress and life satisfaction were assessed using single items; and sleep efficiency using the Consensus Sleep Diary. Results: Both patients and caregivers reported poor sleep efficiency (86% and 82%), moderate levels of life satisfaction, and low levels of stress. At univariate analysis level, only among patients, greater satisfaction, and less stress, correlated with better sleep efficiency (|r| > .19). Dyadic multilevel modeling with lagged design was employed to predict one's sleep efficiency on a given day by the person's stress and satisfaction and the partner's stress and satisfaction on the same day and on the previous day. The results revealed that patients' better sleep efficiency was predicted by caregivers' greater stress on the same day (B=.03, p=.04), but not by other variables. Caregivers' sleep efficiency, however, was not significantly predicted by variables studied. Conclusion: The preliminary findings support the accumulating evidence that poor sleep efficiency is common not only among cancer survivors but also their sleep partner caregivers. Findings also support the premise that sleep is a dyadic concern. Future studies must replicate the current investigation with a larger sample and examine other psychosocial and behavioral factors occurred during day time that might affect sleep as well as the couples' relationship quality, which will provide useful information for clinical and research practices. Support (If Any): Miami CTSI